Case report: Successful treatment of non-bullous lichen planus pemphigoides with dupilumab - Li, Si-Zhe; Xie, Ying-Han; Wang, Si-Hang; Fang, Rou-Yu; Jin, Hong-Zhong; Zuo, Ya-Gang (Frontiers in Medicine, 2022)
Lichen Planus pemphigoides (LPP) is a rare autoimmune bullous disease, characterized by the coexistence of lichen planus and subepidermal bullae. However, the minority of LPP patients could present with papules rather than vesicles or blisters, which is defined as non-bullous LPP. The diagnosis of LPP relies on manifestations, histopathology, serological assay, and direct immunofluorescence of linear disposition of IgG and/or C3 at the basement membrane zone. Up to now, no standard therapeutic strategies have been proposed for the treatment of LPP. Herein, we describe an uncommon non-bullous LPP patients with widespread papules and erythema, probably induced by vaccination. During the hospitalization, he had a poor response to the conventional treatment of topical and systemic corticosteroids, and finally alleviated by an addition of dupilumab. For LPP patients with a traditional medication failure, or were not suitable for a higher dose of corticosteroids, a combination with dupilumab could be an alternative option.